Biocoloniality: Challenges to Religions and Spiritualities - Valverde Campos, Juan Carlos (2021)
The ecological crisis imposes concrete challenges to theologies, religions and spiritualities that cannot be fairly assumed on our continent until a clear awareness of the biocoloniality to which they are being subjected has become clear. The classical theologies that serve as a foundation for Western or Westernized religions and spiritualities spread an equivocal image of God, the world, and the human being. The proposals of the new paradigm of complexity are very useful for reconstructing the fragmented reality that has been transmitted to us in theology.